VD_FINDINFO HC / 2019 / 1142 vom 14. Februar 2020 - VD Tribunal cantonal (2020)
CONTRAT D'ENTREPRISE, AVIS DES DÉFAUTS, RÉCEPTION DE L'OUVRAGE, SÛRETÉS, RETARD | 363 CO, 367 al. 1 CO, 368 CO, 372 al. 1 CO